Technical report: controlling total energy and potential saving cost of water use in shower head using mathematical equation / Nirwana Mat Dawod - Mat Dawod, Nirwana (2017)
The purposes of this study was to controlling the amount of water flow by compare the relationship between flow rate, velocity, hole diameter, number of holes, pipe diameter, value of Reynolds number, friction factor, energy used and cost of savings. The energy consumption at the shower head were calculated using continuity equation and Bernoulli equation. Meanwhile calculation cost of water use per 2 month was done by using the mathematical equation provided by David Public Works Department. This paper analyzed eight types of shower head. In this project, analyzed the different type of shower head indicated that shower head of Type 5 is the best model to reduce energy consumption during shower in which has the low value of resistance factor, f. Meanwhile shower head type 1 and 2 is the best two model to reduce the cost of water by just using for about 3.8 cost of water use compare than other types of shower head. Further analysis for this shower heads have been conducted and shows that shower head Type 1,2 and Type 5 is the best models to make the correction in order to reduce the energy and cost of water used. I have speculated that these difference are affected respectively by hole diameter, pipe diameter, velocity of water and flow rate.